The implementation of osmosis practicum during the COVID-19 pandemic - Lissa Lissa; Nur Subkhi; Ipah Budi Minarti (Universitas Wiralodra, 2022)
Biology lessons conducted online during the COVID-19 pandemic have hampered school implementation practicum activities. Therefore, it is necessary to conduct research that aimed to describe the implementation of biology practicum during online learning. This research was conducted to determine the impact of online osmosis practicum during the COVID-19 pandemic in class XI MIPA 4 SMA Negeri 1 Sindang with a sample of 27 students of class XI MIPA 4 and 1 biology teacher. The method used in this research is descriptive qualitative. The sampling technique was carried out by the purposive sampling method. The instruments used are observation sheets, questionnaire sheets, interview sheets, documentation, and field notes. The data analysis technique used is descriptive qualitative analysis. The osmosis practicum process is carried out independently by students using the guidance from the teacher provided. The practicum results are then reported in an activity video, and the teacher will check the video. The results of the research carried out showed that the implementation of the osmosis practicum went well. The readiness of the tools and practicum materials is in the very good category, students' understanding of doing practicum is in a good category, the conclusions are in a good category, and the practicum report is in the very good category. From the results obtained, it can be concluded that the implementation of the osmosis practicum in class XI MIPA SMA Negeri 1 Sindang was carried out online is implemented properly and effectively.